2019
DOI: 10.18203/2320-1770.ijrcog20194384
|View full text |Cite
|
Sign up to set email alerts
|

A clinical study on fetomaternal outcome in jaundice with pregnancy

Abstract: Background: Jaundice in pregnancy and pregnancy in women with preexisting liver disease is not very uncommon. However it takes a major toll on health of both mother and fetus, due to increased morbidity and mortality for both mother and fetus, categorizing pregnancy as a high risk one. The distribution of jaundice in pregnancy varies throughout the world, but is seen more in developing countries. The course and outcome of liver disorder in pregnancy is altered due to various hemodynamic, hormonal and immunolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
0
0
Order By: Relevance
“…According to the Ministry of Health and Family Welfare Department of India during 2016-2018, the maternal mortality rate in India was 0.11% [9]. Many studies have reported different maternal mortality rates due to abnormal LFTs, with a mean value of approximately 12.6% [10][11][12]. Assuming an alpha error of 5%, a study power of 80%, and a lost-to-follow-up rate of 10%, the necessary sample size was calculated to be 59 patients in each arm of the study.…”
Section: Sample Size Calculationmentioning
confidence: 99%
“…According to the Ministry of Health and Family Welfare Department of India during 2016-2018, the maternal mortality rate in India was 0.11% [9]. Many studies have reported different maternal mortality rates due to abnormal LFTs, with a mean value of approximately 12.6% [10][11][12]. Assuming an alpha error of 5%, a study power of 80%, and a lost-to-follow-up rate of 10%, the necessary sample size was calculated to be 59 patients in each arm of the study.…”
Section: Sample Size Calculationmentioning
confidence: 99%